iPSC line DHMCi010-A is derived from a hereditary nephrotic syndrome patient with an autosomal recessive NPHS2 mutation - Matthes, Robert; Tabatabaeifar, Mansoureh; Burau, Karin; Schaefer, Franz; Jung-Klawitter, Sabine (Stem cell research, 2025)
Recessive mutations in the NPHS2 gene, encoding the podocyte membrane protein podocin, are the most common genetic cause of childhood-onset nephrotic syndrome. To generate induced pluripotent stem cells (iPSCs), peripheral blood mononuclear cells (PBMCs) from a male patient with a homozygous NPHS2 mutation (c.413G>A(;)(c.413G>A)) were reprogrammed using the Cytotune®-iPSC 2.0 Sendai Reprogramming Kit (Invitrogen). The resulting iPSCs exhibit normal morphology and karyotype, express undifferentiated hPSC state markers, and demonstrate the capacity for spontaneous differentiation into all three germ layers in vitro.
Gesehen am 15.01.2026